2014
DOI: 10.1124/mol.113.088575
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Dioxin Imprints Sexual Immaturity of the Pups through Fixing the Status of the Reduced Expression of Hypothalamic Gonadotropin-Releasing Hormone

Abstract: Our previous studies have shown that treatment of pregnant rats with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD; 1 mg/kg) at gestational day (GD) 15 reduces the pituitary synthesis of luteinizing hormone (LH) during the late fetal and early postnatal period, leading to the imprinting of defects in sexual behaviors at adulthood. However, it remains unclear how the attenuation of pituitary LH is linked to sexual immaturity. To address this issue, we performed a DNA microarray analysis to identify the gene(s) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…TCDD, a congener of dioxin, is considered the most toxic environmental contaminant [38], is capable of inducing several adverse effects on human health [26,43,44], exerts estrogenic, antiestrogenic and anti-androgenic activities, depending on dose and time of exposure [45], and is able to perturb the normal development of the hypothalamus, leading to alterations in sexual differentiation [46]. It is known that this compound can be transferred to developing organisms through the placenta or by lactation [6], although we have not measured TCDD in milk.…”
Section: Discussionmentioning
confidence: 99%
“…TCDD, a congener of dioxin, is considered the most toxic environmental contaminant [38], is capable of inducing several adverse effects on human health [26,43,44], exerts estrogenic, antiestrogenic and anti-androgenic activities, depending on dose and time of exposure [45], and is able to perturb the normal development of the hypothalamus, leading to alterations in sexual differentiation [46]. It is known that this compound can be transferred to developing organisms through the placenta or by lactation [6], although we have not measured TCDD in milk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in mammals (Wu et al , 2004; Okino et al , 2006; McClure et al , 2011; Singh et al , 2011; Manikkam et al , 2012a; Manikkam et al , 2012b; Takeda et al , 2012; Somm et al , 2013; Takeda et al , 2014) and zebrafish (Olsvik, et al, 2014) have demonstrated that exposure to TCDD alters DNA methylation patterns not only in the exposed generation, but also in subsequent generations. However, the mechanism of action by which toxicants affect DNA methylation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Humans are exposed to dioxins on a daily basis, and those living in more industrialised countries have an increased exposure (Schecter et al 2003). Exposure to dioxins, especially during pregnancy, had adverse effects in rats, as indicated by both behavioural (Takeda et al 2014) and reproductive parameters (Bjerke and Peterson 1994). 5 per group).…”
Section: Discussionmentioning
confidence: 99%